POLITIK KEBIJAKAN DI SEKTOR PERTAMBANGAN:: Dinamika Implementasi Kebijakan CnC di Kabupaten Pasaman Barat - Elsi, Sutri Destemi (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2018)
This study aims to describe and analyze the implementation of CnC (Clean and Clear) policy in West Pasaman District and find out what factors influence it. The importance of this CnC policy is as a government effort to realize sustainable mining. The theory used is Merilee S. Grindle's policy implementation theory and Krueger's rent seeking theory by using qualitative descriptive methods through in-depth interview techniques, observation and documentation. To test the validity and reliability of the data, 3P (person, place, paper) triangulation techniques and triangulation methods were used The results of this study indicate that the implementation of CnC policy in Pasaman Barat Regency has not been implemented well because the mining governance is not in accordance with the principle of sustainable mining. The failure of CnC policy implementation in Pasaman Barat Regency is influenced by factors of policy content, policy environment and rent seeking behavior. From the contents of the policy, the CnC policy is not applied to all mining companies so that the desired changes have not yet been realized, other than that the Mining and Energy Service as an implementor does not have sufficient quantity and quality resources. Whereas from the policy environment, there are some obstacles in its implementation due to the behavior of the actors in the implementation phase of CnC policies that violate the rules and are not responsive to the community, supported by the disobedience of the mining businessmen in carrying out their obligations